China's environmental foreign relations - Wang-Kaeding, Heidi (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Over recent decades, China has moved from being a follower towards taking on a leadership role in global environmental governance. This book discusses this important development. It examines the key role of Chinese interest groups, showing how through various domestic dynamics they have influenced how China has approached issues such as climate change and the environment. Focusing on examples of multilateral environmental treaties, bilateral cooperation, and the proposition of alternative norms - the idea of China as an "ecological civilisation" - the book provides crucial insights on the evolution of China's approach to international relations and engagement with global environmental governance, and contributes to the discussion of what kind of power China is poise d to become"--
Interest groups in China's environmental foreign relations -- From ecological modernisation to environmental nationalism -- A tale of two treaties -- Selective sharing in bilateral environmental cooperation -- The rise of ecological civilisation -- Conclusion : a constructivist utilitarian power?.
OCLC-licensed vendor bibliographic record.
Keywords: Environmental policy -- China; Environmental protection -- China; Environmental policy -- International cooperation; Environmental protection -- International cooperation; Pressure groups -- China; China -- Foreign relations -- 21st century